(untitled) (Analysis in Theory and Applications, 2017)
In this paper, we have studied the Lacunary type of polynomials and proved a result which generalizes as well as refines some well-known polynomial inequalities regarding the growth of polynomials not vanishing inside a circle. Further, the paper corrects the proofs of some already known results.